Conciencia corporal en el desarrollo de habilidades motrices en estudiantes de primer ciclo de la Facultad de Cultura Física, Deporte y Recreación de la Universidad Santo Tomás (2018)
This research stems according to the concern generated in the author of the article to demonstrate the performance of students in different classes as dancistic Arts, Artistic and Corporal Expression and training some different selections of the University, also the ignorance and the lack of interest that exists not only students but also the teachers of the Faculty of Physical Culture, Sport and Recreation at the University Santo Tomás address the issue of body awareness and movement. On the basis of the importance of both issues and the difference that would be generated not only practitioners of different sports to do them, but also the ability to implement in their classes these both practical and theoretical knowledge.